Frequency of metabolic syndrome in stroke: a study in a tertiary health care centre in north Kerala - P. K., Swapna (International Journal of Research in Medical Sciences, 2017)
Background: Stroke is a leading cause of death and disability in developing countries beginning to affect young adults. Key components of the metabolic syndrome are important risk factors for stroke. This study intended to study the prevalence of metabolic syndrome in patients with stroke. Screening adolescents and young adults for components of metabolic syndrome will prove useful in clinical management, and its elements ultimately become important therapeutic targets for the reduction of stroke burden in the general population. Methods: Data was collected from 150 patients who were admitted with cerebrovascular accident (CVA) in the Department of Medicine. Frequency tests were conducted for various risk factors. Chi-square and Fisher exact test were used to test the significance of proportion of study parameters in the classes. The observations in this study were analysed using SPSS software. Results: Metabolic syndrome was present in 46% of the study population. Among the components of the metabolic syndrome, Hypertension was the most prevalent risk factor (68%). 67.14% of the population had 2 components of metabolic syndrome which predisposes them to a greater risk of developing metabolic syndrome over a period of few months to years. Conclusions: With the obesity epidemic, the impact of the metabolic syndrome is likely to increase. Thus, diagnosing and adequately managing metabolic syndrome is an important step in the preventing cerebrovascular disease. This study emphasises the need to target the population with one or more components of the metabolic syndrome as they are at high risk of developing stroke in the future.